Prospects for realizing international women’s rights law through local governance: the case of cities for CEDAW - Runyan, Anne Sisson (Human rights review, 2021)
How best to realize international human rights law in practice has proved a vexing problem. The challenge is compounded in the USA, which has not ratified several treaties including the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). The Cities for CEDAW movement addresses this deficit by encouraging cities to endorse and implement CEDAW norms. In doing so, it seeks to catalyze a local boomerang effect, whereby progressive political momentum at the local level generates internal pressure from below to improve gender equity outcomes across the country and eventually, at the national level. In this article, we trace the diffusion of Cities for CEDAW activism with attention to the case of Cincinnati and analyze its implications for advancing women’s rights principles. We argue that while Cities for CEDAW has potential to enhance respect for women’s rights in local jurisdictions, its impact on national policy remains limited.